2013
DOI: 10.1111/bij.12138
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cases of asymmetric introgression among horseshoe bats detected by phylogenetic conflicts across loci

Abstract: Phylogenetic discordance among taxa can provide powerful insights into past episodes of introgressive hybridization, as well as lineage sorting. Previously, we showed that the taxonomically distinct taxon Rhinolophus sinicus septentrionalis has undergone historical introgression with its sympatric sister subspecies Rhinolophus sinicus sinicus. To examine in more detail the extent of gene flow between these two taxa, and also between these and their sister species Rhinolophus thomasi, we obtained new samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 68 publications
3
18
0
4
Order By: Relevance
“…This structural variation suggests that the Central sinicus is more closely related to septentrionalis than to the other two sinicus taxa, a finding that is consistent with previous results based on two mtDNA protein coding genes [34]. The shared absence of repeated motifs in Central sinicus and septentrionalis could arise from introgression of the complete mitochondrial genome from septentrionalis to Central sinicus , as suggested previously [33], [34]. Alternatively, this simple structure could suggest that the Central sinicus and septentrionalis represent the ancestral form before R. sinicus diverged into several taxa, although why this has been retained whereas more complex repeated sequences have evolved in East sinicus and Hainan sinicus , is not known.…”
Section: Discussionsupporting
confidence: 91%
“…This structural variation suggests that the Central sinicus is more closely related to septentrionalis than to the other two sinicus taxa, a finding that is consistent with previous results based on two mtDNA protein coding genes [34]. The shared absence of repeated motifs in Central sinicus and septentrionalis could arise from introgression of the complete mitochondrial genome from septentrionalis to Central sinicus , as suggested previously [33], [34]. Alternatively, this simple structure could suggest that the Central sinicus and septentrionalis represent the ancestral form before R. sinicus diverged into several taxa, although why this has been retained whereas more complex repeated sequences have evolved in East sinicus and Hainan sinicus , is not known.…”
Section: Discussionsupporting
confidence: 91%
“…As a consequence, vicariant populations adaptively evolved under different ecological selections imposed by isolated refugia which may have led to shifts in their morphology (noseleaf structure and body, skull, glans penis, and baculum morphology) and echolocation systems, and subsequently their own SMRSs. Depending on the status of SMRSs of each taxon, the restoration of connectivity between some of those during interglacial periods allowed ancient introgression events between some taxa that retained their relatedness (Mao, Zhang et al., ; Mao, He et al., ; Mao, Thong et al., ). However, to test this hypothesis, further investigations including genetic analyses of both mitochondrial and nuclear genomes are needed (Berthier et al., ; Hassanin et al., ; Mao, Zhang et al., ; Nesi et al., ; Tu et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In China, R. sinicus is widely distributed in the Southwest, Central, and Eastern regions, as well as in Hainan Island (Csorba, Ujhelyi, & Thomas, ). Previous studies based on multilocus datasets have revealed high genetic differentiation and strong phylogeographic structuring within R. sinicus (Mao, He, Zhang, Rossiter, & Zhang, ; Mao, Thong, et al., ). The bats from East China, the offshore Hainan Island and Vietnam formed a highly supported lineage, which separated from those lineages in Central China and Yunnan (Mao, Thong, et al., ).…”
Section: Introductionmentioning
confidence: 95%
“…Previous studies based on multilocus datasets have revealed high genetic differentiation and strong phylogeographic structuring within R. sinicus (Mao, He, Zhang, Rossiter, & Zhang, ; Mao, Thong, et al., ). The bats from East China, the offshore Hainan Island and Vietnam formed a highly supported lineage, which separated from those lineages in Central China and Yunnan (Mao, Thong, et al., ). Among those lineages of R. sinicus , the morphological data and echolocation call frequencies are different, although there is considerable overlap.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation